Comparisons of external fixator combined with limited internal fixation and open reduction and internal fixation for Sanders type 2 calcaneal fractures: Finite element analysis and clinical outcome. Issue 7 (July 2017) - Pan, M.; Chai, L.; Xue, F.; Ding, L.; Tang, G.; Lv, B.
Abstract : Objectives: The aim of this study was to compare the biomechanical stability and clinical outcome of external fixator combined with limited internal fixation (EFLIF) and open reduction and internal fixation (ORIF) in treating Sanders type 2 calcaneal fractures. Methods: Two types of fixation systems were selected for finite element analysis and a dual cohort study. Two fixation systems were simulated to fix the fracture in a finite element model. The relative displacement and stress distribution were analysed and compared. A total of 71 consecutive patients with closed Sanders type 2 calcaneal fractures were enrolled and divided into two groups according to the treatment to which they chose: the EFLIF group and the ORIF group. The radiological and clinical outcomes were evaluated and compared. Results: The relative displacement of the EFLIF was less than that of the plate (0.1363 mm to 0.1808 mm). The highest von Mises stress value on the plate was 33% higher than that on the EFLIF. A normal restoration of the Böhler angle was achieved in both groups. No significant difference was found in the clinical outcome on the American Orthopedic Foot and Ankle Society Ankle Hindfoot Scale, or on the Visual Analogue Scale between the two groups (p > 0.05). Wound complications were more common in those who were treated with ORIF (p = 0.028). Conclusions: Both EFLIF and ORIF systems were tested to 160 N without failure, showing the new construct to be mechanically safe to use. Both EFLIF and ORIF could be effective in treating Sanders type 2 calcaneal fractures. The EFLIF may be superior to ORIF in achieving biomechanical stability and less blood loss, shorter surgical time and hospital stay, and fewer wound complications. Cite this article : M. Pan, L. Chai, F. Xue, L. Ding, G. Tang, B. Lv. Comparisons of external fixator combined with limited internal fixation and open reduction and internal fixation for Sanders type 2 calcaneal fractures: Finite element analysis and clinical outcome. Bone Joint Res 2017;6:433–438. DOI: 10.1302/2046-3758.67.2000640.